The invisible Fran - Benton, Jim (New York : Simon & Schuster Books for Young Readers, 2011)
When Franny Stein, self-styled mad scientist, creates a robot to show her school friends the joys of science, she ends up learning something from them instead.
Reprint. Originally published: c2004.
Keywords: Science -- Experiments -- Fiction; Robots -- Fiction; Individuality -- Fiction; Schools -- Fiction; Science -- Experiments -- Fiction; Robots -- Fiction; Individuality -- Fiction; School stories